2010
DOI: 10.1111/j.1523-5378.2010.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Monoclonal Stool Tests for Determining Cure of Helicobacter pylori Infection After Treatment

Abstract: All monoclonal fecal tests in this series presented similar performance in the post-treatment setting. A negative test after treatment adequately predicted cure of the infection. However, nearly a third of tests were false positive, showing a poor predictive yield for persistent infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
(100 reference statements)
0
15
1
3
Order By: Relevance
“…A meta-analysis showed that Page 11 of 39 A c c e p t e d M a n u s c r i p t 11 the laboratory ELISA monoclonal SAT has a similar high accuracy for both the initial and post-treatment diagnosis (37). The rapid in-office monoclonal SAT, based on an immunochromatographic technique, seems to be less accurate (38).…”
Section: Non-invasive Testsmentioning
confidence: 98%
“…A meta-analysis showed that Page 11 of 39 A c c e p t e d M a n u s c r i p t 11 the laboratory ELISA monoclonal SAT has a similar high accuracy for both the initial and post-treatment diagnosis (37). The rapid in-office monoclonal SAT, based on an immunochromatographic technique, seems to be less accurate (38).…”
Section: Non-invasive Testsmentioning
confidence: 98%
“…These data have been confirmed by more recent studies 78 79. In contrast, the rapid in-office tests have a limited accuracy 80 81…”
Section: Management Of H Pylori Infection (Workhop 2)mentioning
confidence: 99%
“…Por otra parte, como se señala más adelante, la fiabilidad diagnóstica de los distintos métodos de detección en heces varía en función del fabricante y de los aspectos técnicos, y los resultados en nuestro medio son ligeramente inferiores a los observados con la prueba del aliento 157,161,162 . Por esto y por la necesidad de validación local, se prefiere la prueba del aliento a las pruebas en heces como técnica de elección para diagnosticar de forma no invasiva la infección por H. pylori 161,162 .…”
Section: Recomendación B1unclassified
“…De hecho, la fiabilidad de las pruebas diagnósticas para H. pylori en heces es alta, siempre que se utilicen pruebas monoclonales y se eviten las pruebas inmunocromatográficas rápidas 54,157,161,162 . Sin embargo, como se ha mencionado previamente, la fiabilidad diagnós-tica de los distintos métodos de detección en heces varía en función del fabricante y la técnica empleada, y los resultados en nuestro medio son ligeramente inferiores a los que se han descrito con la prueba del aliento utilizada en condiciones óptimas 157,161,162 . Dos inconvenientes adicionales son que las pruebas en heces son menos aceptadas tanto por los pacientes como por el personal sanitario y que la mayoría de pruebas en heces actualmente disponibles no han sido suficientemente validadas en nuestro medio.…”
Section: Recomendación B2unclassified
See 1 more Smart Citation